KONTEKTUALISASI RASA AMAN PEREMPUAN YANG MELAKUKAN SAFAR TANPA MAHRAM PERSPEKTIF HADIS - Misbah Mrd; Dahliati Simanjuntak (Yayasan Baitul Hikmah al-Zain, 2024)
Discussing the hadith about women's journey without a mahram is often discussed by Islamic scholars. There are many differences of opinion which have been explained in the hadiths of the Prophet SAW. which looks authentic and can be used as a guide for readers. The classification of mahram in Islam also includes factors such as lineage, marriage and breastfeeding. In the hadith books explained by Islamic scholars it does not eliminate the textual meaning of mahram. In the Qur'an, mahram is explained in Surah An-Nisa' verses 23-24. In the context of women traveling without a mahram, many scholars do not allow it, because they are worried that women will not be able to maintain their honor. When women travel without a mahram in an emergency, it is permissible.